Encyclopedia of nature - Dorling Kindersley Multimedia (New York DK Multimedia, 1997)
Provides interactive exploration of the fascinating lives of hundreds of species of animals and plants and the habitats in which they live. Includes video sequences, animation, photographs, bird calls, a 3D interface and over 1800 articles.
Title from disc surface.
Ed. statement from disc surface.
Title on container: Eyewitness encyclopedia of nature 2.0.
Includes book: Nature facts / written by Scarlett O'Hara. DK Publishing, 1997.
System requirements for Windows: 486DX/33MHz CPU; 8 Mb RAM; 22 Mb available space on hard drive; Windows 3.1x or Windows 95; 640 x 480 (800 x 600 recommended) 256 color screen display; double-speed CD-ROM drive; 8-bit sound card; loudspeakers or headphones; mouse.
Systems requirements for Macintosh: 68LC040 25 MHz; 12 Mb RAM; 16 Mb available space on hard drive (recommended); System 7.0+; 640 x 480 (800 x 600 preferred) 256 color screen display; double-speed CD-ROM drive; 8-bit audio; loudspeakers or headphones; mouse.
Keywords: Natural history|vInteractive multimedia; Nature study|vInteractive multimedia